N-Heterocyclic Carbene Catalyzed Reassembly of Dibenzyl Ethers: Facile Access to α-Hydroxy Ketones - Li, Zheyao; Ju, Lei; Bao, Ruipeng; Lin, Xinbo; Wang, Teng; Yu, Xinhong (Synlett, 2024)
A novel one-pot cascade process of oxidation-initiated, N-heterocyclic carbene catalyzed, reintegration of dibenzyl ethers has been developed for the first time. This protocol allows straightforward access to α-hydroxy ketones from dibenzyl ethers. It is noteworthy that the present method is the first attempt to synthesize benzoin from dibenzyl ether.
Keywords: N-heterocyclic carbenes; dibenzyl ethers; hydroxy ketones; ethers; oxidation; benzoin condensation